Political Action Committees: Fact, fancy, and morality - Banthin, Joanna (Journal of business ethics, 1986)
The analysis of Political Action Committee activities is dominated by the perspective that PAC contributions are a rational investment in political candidates; they yield valuable short-term payoffs. PACs buy access to officeholders and their votes on important legislation. Despite broad acceptance of this morally suspect theory, the evidence upon which it is based is weak. An alternative perspective — what we call the principled approach — both fits the evidence and rejects the morally repugnant interpretation of the relationship between business and politics that permeates the rational investment perspective.